Privacy online perspectives on privacy and self-disclosure in the social web - Trepte, Sabine; Reinecke, Leonard (Springer, 2011)
Communications and personal information that are posted online are usually accessible to a vast number of people. Yet when personal data exist online, they may be searched, reproduced and mined by advertisers, merchants, service providers or even stalkers. Many users know what may happen to their information, while at the same time they act as though their data are private or intimate. They expect their privacy will not be infringed while they willingly share personal information with the world via social network sites, blogs, and in online communities. The chapters collected by Trepte and Reinecke address questions arising from this disparity that has often been referred to as the privacy paradox. Works by renowned researchers from various disciplines including psychology, communication, sociology, and information science, offer new theoretical models on the functioning of online intimacy and public accessibility, and propose novel ideas on the how and why of online privacy. The contributing authors offer intriguing solutions for some of the most pressing issues and problems in the field of online privacy. They investigate how users abandon privacy to enhance social capital and to generate different kinds of benefits. They argue that trust and authenticity characterize the uses of social network sites. They explore how privacy needs affect users? virtual identities. Ethical issues of privacy online are discussed as well as its gratifications and users? concerns. The contributors of this volume focus on the privacy needs and behaviors of a variety of different groups of social media users such as young adults, older users, and genders. They also examine privacy in the context of particular online services such as social network sites, mobile internet access, online journalism, blogs, and micro-blogs. In sum, this book offers researchers and students working on issues related to internet communication not only a thorough and up-to-date treatment of online privacy and the social web. It also presents a glimpse of the future by exploring emergent issues concerning new technological applications and by suggesting theory-based research agendas that can guide inquiry beyond the current forms of social technologies.